2012
DOI: 10.1063/1.3701588
|View full text |Cite
|
Sign up to set email alerts
|

Few electron double quantum dot in an isotopically purified 28Si quantum well

Abstract: We present a few electron double quantum dot device defined in an isotopically purified 28 Si quantum well (QW). An electron mobility of 5.5 · 10 4 cm 2 (Vs) −1 is observed in the QW which is the highest mobility ever reported for a two-dimensional electron system in 28 Si. The residual concentration of 29 Si nuclei in the 28 Si QW is lower than 10 3 ppm, at the verge where the hyperfine interaction is theoretically no longer expected to dominantly limit the T 2 spin dephasing time. We also demonstrate a compl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 22 publications
(23 reference statements)
0
30
0
Order By: Relevance
“…30 Hereof only 29 Si has nonzero nuclear spin (I = 1/2), and purification can further reduce its abundance down to 0.05%. 31,32 For this reason, silicon-based quantum dots have become the new focus of interest, and recent progress emphasizes their perspectives. [33][34][35][36] Another advantage of silicon 8,29 over GaAs is a larger g factor, which allows spin manipulations in smaller magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…30 Hereof only 29 Si has nonzero nuclear spin (I = 1/2), and purification can further reduce its abundance down to 0.05%. 31,32 For this reason, silicon-based quantum dots have become the new focus of interest, and recent progress emphasizes their perspectives. [33][34][35][36] Another advantage of silicon 8,29 over GaAs is a larger g factor, which allows spin manipulations in smaller magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated for Si/SiGe QPCs defined by gate electrodes placed on a Al 2 O 3 insulated Si surface, i.e., metaloxide-semiconductor (MOS), that negatively biasing a global top gate gradually reduces the charge noise in the conductance. 17 The charge noise may be more significant in surface Schottky gate structures than in MOS gate structures because there is no direct leakage between the gate metal and the QPC channel in the latter, but no detailed studies on charge noise spectra in Si/SiGe QPCs have been reported to date.…”
mentioning
confidence: 99%
“…This mobility may be the highest reported for modulation-doped Si 2DEGs grown by CVD regardless of 28 Si enrichment. In previous work of isotopically-enriched 28 Si 2DEGs grown by molecular beam epitaxy, the highest reported mobility was 55 000 cm 2 /V-s. 12 Enhancement-mode samples with enriched 28 Si only in the Si QW layer were made without n-type dopants with a SiGe setback layer of 60 or 150 nm on top of the 2DEG layer (Table I). With a metal gate of Cr/Au on top of 90-nm Al 2 O 3 , the Hall electron density increased with gate voltage and mobility increased rapidly with electron density (Fig.…”
mentioning
confidence: 99%